ChemInform Abstract: Kinetic Study on Solid‐Phase Reduction of Silica‐Supported Nickel Oxide Species. Issue 9 (February 2016) - Yamashita, Shohei; Yamamoto, Yusaku; Katayama, Misaki; Inada, Yasuhiro
Abstract: Review: 44 refs.